The effect of game-based approaches on decision-making, knowledge, and motor skill: A systematic review and a multilevel meta-analysis - Manninen, Mika; Magrum, Eric; Campbell, Sara; Belton, Sarahjane (European physical education review, 2025)
This study aimed to compare the effect between game-based approaches (GBAs) and traditional skill approaches on decision-making, knowledge and motor skill in physical education students and athletes. A systematic review and meta-analysis of experimental studies available before October 2023 was conducted. The initial search yielded 8431 articles, with 28 articles (n = 1600) meeting the inclusion criteria. Studies were analyzed using three-level random-effects models with a robust variance estimation. Outcomes were computed as raw mean differences and Hedges’s g effect sizes. Results indicate that GBAs have a positive heterogeneous effect on decision-making in game situations (ES = 11.41%; 95% CI [4.39, 18.43]) and motor skill in skill tests (g = 0.36; 95% CI [0.14, 0.57]). GBAs did not have an effect on knowledge (g = 0.37; 95% CI [−0.12, 0.86]) or motor skill in game situations (ES = 1.13%; 95% CI [−2.43, 4.68]). Meta-regression analyses revealed that the experience of the interventionist, the quality of the studies, and the comparison condition significantly influence the impact of GBAs on motor skill tests. More detailed and transparent reporting of trials would benefit the field.